Breaking the nap habit: one-year nap restriction mitigates memory decline in older adults - Marine Dourte; Gregory Hammad; Stella de Haan; Mathilde Reyt; Michele Deantoni; Marion Baillet; Alexia Lesoinne; Gilles Vandewalle; Fabienne Collette; Vincenzo Muto; Philippe Peigneux; Christina Schmidt (GeroScience, 2026)

Diurnal dynamics of multilayer brain networks predict cognitive trajectories in aging - Kenza Bennis; Anna Canal-Garcia; Joana B. Pereira; Giovanni Volpe; Francis Eustache; Christophe Phillips; Christine Bastin; Fabienne Collette; Gilles Vandewalle; Thomas Hinault (GeroScience, 2025)

The Effect of Mindfulness-based Programs on Cognitive Function in Adults: A Systematic Review and Meta-analysis - Tim Whitfield; Thorsten Barnhofer; Rebecca Acabchuk; Avi Cohen; Michael Lee; Marco Schlosser; Eider M. Arenaza-Urquijo; Adriana Böttcher; Willoughby Britton; Nina Coll-Padros; Fabienne Collette; Gaël Chételat; et al. (Neuropsychology Review, 2022)
Mindfulness-based programs (MBPs) are increasingly utilized to improve mental health. Interest in the putative effects of MBPs on cognitive function is also growing. This is the first meta-analysis of objective cognitive outcomes across multiple domains from randomized MBP studies of adults. Seven databases were systematically searched to January 2020. Fifty-six unique studies ( n = 2,931) were included, of which 45 ( n = 2,238) were synthesized using robust variance estimation meta-analysis. Meta-regression and subgroup analyses evaluated moderators. Pooling data across cognitive domains, the summary effect size for all studies favored MBPs over comparators and was small in magnitude ( g = 0.15; [0.05, 0.24]). Across subgroup analyses of individual cognitive domains/subdomains, MBPs outperformed comparators for executive function ( g = 0.15; [0.02, 0.27]) and working memory outcomes ( g = 0.23; [0.11, 0.36]) only. Subgroup analyses identified significant effects for studies of non-clinical samples, as well as for adults aged over 60. Across all studies, MBPs outperformed inactive, but not active comparators. Limitations include the primarily unclear within-study risk of bias (only a minority of studies were considered low risk), and that statistical constraints rendered some p -values unreliable. Together, results partially corroborate the hypothesized link between mindfulness practices and cognitive performance. This review was registered with PROSPERO [CRD42018100904].